Peculiarities of physical abilities development in hearing-impaired students with different types of temperament who started adaptive soccer lessons - Bobkov G.S.,; Kachenkova E.S. ,; Medvedev I.N. ,; Zvereva M.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study. This work is aimed at determining the specifics of the dynamics of physical fitness in students with hearing impairment, differing in temperament type, after starting classes in the adaptive football section. Methods and structure of the study. The present study involved 78 young men with hearing impairments who are second- and third-year university students and have started classes in the adaptive football section. In the course of the work, such methods as questionnaires, testing and mathematical analysis were used, including the calculation of the Student's t-test. Results and conclusions. Initially, the physical fitness of students with hearing impairments and different types of temperament was significantly different. These differences remained noticeable even after the start of regular football practice. Phlegmatic students showed the best indicators of general and strength endurance, surpassing students with other temperaments. At the same time, choleric patients had the most developed ability to maintain dynamic balance, outperforming others in this parameter. It is advisable to use these data in universities to optimize the physical fitness of hearing-impaired students in physical education classes. Adapting football training to suit each student's temperament can help improve their athletic performance through an individualized approach. This approach will make it possible to more effectively develop the necessary physical qualities, taking into account the characteristics of each type of temperament.